Assessing the proposed pre-last glacial maximum human occupation of North America at Coats-Hines-Litchy, Tennessee, and other sites. (15th April 2018) - Tune, Jesse W.; Waters, Michael R.; Schmalle, Kayla A.; DeSantis, Larisa R.G.; Kamenov, George D.
Abstract: Genomic studies indicate that the first Pleistocene foragers who entered North America diverged from ancestral populations in Beringia sometime after the Last Glacial Maximum (LGM); however, several archaeological sites in North America have been proposed to predate the LGM. We present the results of our excavation and analysis of one such site, Coats-Hines-Litchy, Tennessee, which show that this site is a paleontological locality containing a geofact assemblage that pre-dates the LGM. Other sites in North America that purportedly predate the LGM occur in geomorphic contexts that are also conducive to the formation of geofact assemblages. As such, we propose that the reported artifacts from these sites were created by natural processes. No sites in North America currently provide credible evidence of a pre-LGM occupation. Highlights: Coats-Hines-Litchy is a paleontological locality pre-dating the LGM. Natural processes created geofact assemblages at many pre-LGM sites in the Americas. No sites in North America currently provide credible evidence of a pre-LGM occupation. Genomic and archaeological data support a post-LGM human migration into the Americas.